Comparative transcriptomics of two petal variants reveals key functional genes underlying petal shape development in lotus (Nelumbo) - He, Jiaxin; Ma, Yini; Liu, Qingqing; Zhang, Rui; Huang, Guohong; Zhang, Dasheng; Liu, Fengluan; Yang, Caixia (Frontiers in Plant Science, 2025)
IntroductionThe lotus (Nelumbo Adans.) is a versatile plant that integrates ornamental beauty, culinary applications, medicinal benefits, ecological significance, and cultural symbolism. However, its ornamental value is somewhat restricted by the relatively limited diversity in petal shapes. Consequently, it is essential to explore the genes regulating petal shape, in order to lay a primary foundation for molecular-assisted breeding of lotus cultivars with novel petal shapes.MethodsThis study focused on two variants with distinct petal shapes: the broad petals of N. lutea M512 and the narrow petals of N. nucifera ‘Chenshan Feiyan’ (CSFY). Petal shape differences, including length, width, length-to-width ratio, and epidermal cell density, were compared at four floral bud stages between these variants and their respective wild types. Using RNA-sequencing technology, differentially expressed genes (DEGs) between variant and wild-type petals were identified, followed by gene ontology (GO) and kyoto encyclopedia of genes and genomes (KEGG) enrichment analyses. By integrating the results of morphological and enrichment analysis, key genes involved in the development of wide and narrow petal shapes in lotus were identified.ResultsIt revealed that the broad petal variation of M512 was caused by a reduction in petal length while maintaining width, whereas the narrow petal phenotype of CSFY resulted from a combination of increased length and decreased width. The final petal shapes in both variants were primarily determined by the total number of cells along the petal’s longitudinal (length) and transverse (width) directions, rather than by cell size or shape. A total of 59 and 96 candidate genes associated with petal shape development were identified in broad-petaled M512 and narrow-petaled CSFY, respectively. Many of these genes are directly involved in the development of cell wall/membrane and in the synthesis and metabolic pathways of plant hormones such as cytokinins, auxins, jasmonic acid, and brassinosteroids.DiscussionThe main framework for petal shape was established during stages D1 and D5. The key genes identified in this study will facilitate the development of artificial techniques for petal shape regulation and serve as a theoretical foundation for molecular-assisted breeding in lotus.